Chiral separation and molecular simulation study of six antihistamine agents on a coated cellulose tri‐(3, 5‐dimethylphenycarbamate) column (Chiralcel OD‐RH) and its recognition mechanisms. Issue 14 (5th May 2021) - Liu, Yanru; Wang, Xia; Yu, Jia; Guo, Xingjie
Abstract: Enantiomeric separation of six antihistamine agents was first systematically investigated on a cellulose‐based chiral stationary phase (CSP), that is, cellulose tris‐(3, 5‐dimethyl phenyl carbamate) (Chiralcel OD‐RH), under the reversed‐phase mode. Orphenadrine, meclizine, terfenadine, dioxopromethazine, and carbinoxamine enantiomers were completely separated under the optimized mobile phase conditions with resolutions of 5.02, 1.93, 1.68, 1.67, and 1.54, respectively. Mequitazine was partially separated with a resolution of 0.77. The influences of type and concentration of buffer salt, the pH of buffer solution, and the type and ratio of organic modifier on the chiral separation were evaluated and optimized. For a better insight into the enantiorecognition mechanisms, molecular docking was carried out via the Autodock software. The lowest binding energy and the optimal conformations of the analytes/CSP complexes were supplied, and the mechanisms of chiral recognition were determined. According to the results, the key interactions for the chiral recognition of these six analytes on CDMPC were π–π interactions, hydrophobic interactions, hydrogen bond interactions, and some special interactions.